Spontaneous Tumor Lysis Syndrome in Small-Cell Lung Cancer: A Rare Complication - Weerasinghe, Chanudi (World J Oncol, 2015)
Tumor lysis syndrome (TLS) is a life-threatening condition which consists of a constellation of electrolyte imbalances, acute renal failure, seizure, and arrhythmias. It is most commonly seen with hematologic malignancies after the initiation of chemotherapy. However, it can also occur spontaneously, prior to treatment with cytotoxic agents. TLS has been rarely described with non-hematologic solid tumors, and it is even more uncommon to have spontaneous tumor lysis syndrome (STLS) in solid tumors. To our knowledge, only two cases of STLS in small-cell lung cancer (SCLC) were reported in the literature. Herein, we present the case of a patient with metastatic SCLC who developed STLS. Our case highlights that in the setting of metastatic solid tumors, STLS must be in the differential diagnosis, to allow prompt initiation of prophylaxis and treatment.